The Evaluation Of The Aid Programme Floating Cage And Fish Seed In Sungai Paku Village, Sub-District of Kampar Kiri, Kampar District, Riau Province - Budi Prasojo; Firman Nugroho; Kusai ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This Research is about The Evaluation Of The Aid Programme Floating Cage And Fish Seed In Sungai Paku Village, Sub-District of Kampar Kiri, Kampar District, Riau Province. It was conducted on March 2015 in the Sungai Paku Village Kampar Kiri District Kampar regency Riau Province. This study aimed to evaluate the process of aid programs floating cage and fish seeds in the Sungai Paku Village. Evaluate the result of assistance programs floating cage and seeds fish in the Sungai Paku. Based the result of research I that the submission and the aid receipt of assistance, the identification of the candidates fish farmer of the fish recipients, of delivering aid by the and fishery, supervision and extension of the provincial department of fisheries and marine riau. For evaluation of the results, the aid progamme to help the economy recipients, develop the cultivation of fish cried sustainable and can supply of fish in the region fulfilled.keywords: evaluation , Dinas helps programme, Kampar regency.